El discurso del buen pastor en Juan 10 - Beutler, S.J., Johannes (Cuestiones Teológicas, 2005)
There is no doubt about the importance one should give to the words of the Good Shepherd in John 10. Nevertheless, very few studies have dealt with the dynamics of the narrative, its inner structure and, especially, with its relationship within the context of the fourth Gospel. We know even less about the links of this text with others in the Old Testament, what is said in the Jewish Tradition and other writings between the two Testaments. Needless to say that a close study of these sources will give an exegetical and hermeneutical focus and a new perspective to these words of Jesus. This could also be achieved without overlooking different studies and interpretations of these verses given by worlwide known exegetes.